Analisis Pendapatan Usahatani Kelapa Sawit Di Desa Pinang Damai Kecamatan Torgamba Kabupaten Labuhanbatu Selatan - Pakpahan, Sutriadi; Pulungan, Delyana R. (Jurnal Riset AKuntansi dan Bisnis, 2025)
This research aims to describe oil palm farming activities, determine production costs, revenues, income and the ratio of revenues and costs in oil palm farming. The research was carried out from June to August 2023 in Pinang Damai Village, Torgamba District, South Labuhanbatu Regency. The sampling method used was the probability sampling method. This research collects primary and secondary data. Data analysis was carried out to calculate costs, revenues, income and R/C ratio. The results of this research show that the average production cost is IDR 47,735,874-/farmer/year and the average total revenue is IDR 133,226,785. .-/farmer/year. Meanwhile, the average income per hectare is IDR 25,009,332.-/ha/year with total production costs of IDR 13,957,564.-/ha/year with revenues of IDR 38,966,896.-/ha/year. Oil palm farming in Waru District is economically profitable based on an R/C ratio of 2.8. This means that every cost incurred of IDR 1.- will generate revenues of IDR. 2.8,- so that the business makes a profit